Transformation before the 'Transition' (Employment and Wage Setting in Hungarian Firms 1986-89) - Janos Kollo (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1998)
The paper addresses the question why Hungarian state enterprises cut employment by two-digit percentages in the last years of state socialism. It argues that job destruction was a result of changing incentives and liberties (harder budget constraint, stronger insider power, loosening political restrictions on downsizing) rather than of market-related shocks. Changing the inherited combination of output, employment, and wages could be in the interest of workers, managers, or both parties. The implications for wages and profits were hard to predict but the concievable scenarios of adjustment unanimously implied lower employment. The hypotheses are tested against data on output, employment, wages and profits from a panel of 2666 firms observed in 1986 and 1989.
Keywords: 330